THE FORECAST OF ECONOMIC DEVELOPMENT OF THE REPUBLIC OF KOMI - L.V. Chayka (Экономика региона, 2008)
A methodological approach to forecasting of the macroeconomic dynamics of regional development (of case the Republic of Komi) is presented in the article. The basis of forecast researches is the analysis and modeling dependences of the gross regional product production and distribution. Results of forecast calculations for a period until 2020 are given.